Assessing the psychometric properties of the intrinsic motivation inventory in blended learning environments - Bosch , Chantelle (Journal of Education and e-Learning Research, 2024)
This study investigates the validity and reliability of the Intrinsic Motivation Inventory (IMI) in the context of blended learning. In the digital age, the fusion of online components with traditional classroom instruction has become integral to modern pedagogy, giving rise to blended learning—a flexible approach accommodating diverse learning needs. In such multifaceted environments, intrinsic motivation emerges as pivotal for sustaining student engagement, bridging the gap between in-person and online learning components. Utilizing a quasi-experimental quantitative research design, the research focuses on first-year university students enrolled in a blended learning economics course. Thorough statistical analysis affirms the IMI’s effectiveness in accurately measuring intrinsic motivation levels within the diverse framework of blended learning. The findings not only validate the IMI as a tool for assessing intrinsic motivation but also underscore its importance for educators. Understanding students’ intrinsic motivation is essential for tailoring instructional strategies, identifying at-risk students, and proactively preventing potential dropouts in blended learning environments. The validation of the IMI enhances the accuracy of assessments, interventions, and program evaluations, ultimately contributing to the improvement of education quality for students engaged in the integrated format of traditional and online instruction.